POTENTIOMETRIC BASED LEAD SENSOR TO DETECT THE LEVELS OF LEAD IN BLOOD - Eka Novitasari; Ayu Rahayu Anggraeni; - Muhiroh; Mokhammad W. Dahlan; Ani Mulyasuryani (Institute of Research and Community Services, Universitas Negeri Yogyakarta, 2016)
This study was aimed at determining the optimal conditions of lead sensor in the development of ion lead sensor to perform the optimization of several parameters such as the number of ionophores and membrane thickness. In this study, a lead sensor based on lead selective electrode was developed. The electrode was modiﬁ ed by adding lead sulﬁ de in chitosan membran as an active agent (ionophores) and superimposed on the surface of SPCE. The amounts of PbS added in chitosan solution were 0.5%, 1%, 1.5%, 2%, and 2.5% (w/v). The thickness of membrane used were 15 µm, 20 µm, 45 µm, and 75 µm. The sensors were tested in standard solution at concentration 10 -8 M to 10 M and at pH 2, 3, 4, and 5. Lead sensor has optimum performance on PbS 1.5%, thickness of membrane on 15 µm and pH 4. The Nernst factor obtained was 23.45 mV/decade with the solution concentration range 0.032 ppm to 0.322 ppm.-1